Firm Size, Leverage and Corporate Governance Mediated Intellectual Capital on Firm Performance - Angelia Angelia; Elsa Imelda (Graduate Program of Universitas Tarumanagara, 2023)
This study was conducted to determine the effect of firm size, leverage and corporate governance mediated by intellectual capital on firm performance of food and beverages companies listed on the Indonesia Stock Exchange during the period 2018-2020. The sample used in this study were 36 companies using purposive sampling technique. The results of the analysis show that firm size and corporate governance does not have a significant effect on firm performance, while the leverage have a positive and significant effect on firm performance. Corporate governance does not have a significant effect on intellectual capital, while the firm size and leverage have a significant effect on intellectual capital. Firm size, leverage and corporate governance does not have a significant effect on firm performance using intellectual capital as mediation.